TLA Campus: Youth Group of Turkish Librarians’ Association - Tuğba Kızılöz (Türk Kütüphaneciliği)
In this paper, TLA Campus’s establishment process, mission, vision, information about the events which have been carried out since the establishment of TLA Campus and its future plans and objects are mentioned. The contact information of TLA Campus is also provided.